Episodes of asthma during pregnancy – link with a viral infection and treatment approaches - Pertseva T.A.; Kireyeva T.V.; Kravchenko N.K. (Medičnì Perspektivi)
Bronchial asthma (BA) is the most common respiratory disease in pregnancy. About 20% of pregnant women experience asthma exacerbations of varying severity, while 5.8 % of them require hospitalization. Objective: to study asthma course during pregnancy by determining clinical and functional cha¬racteristics of the disease, taking into account presence of exacerbations and adherence to basic therapy (BT). Materials and methods: The study included 35 pregnant females (Me ± SD) aged 31±5,28 years, gestational age – 34±6,69 weeks. Anamnestic and physical data, spirometry and assessment of asthma control using Control Asthma Test were conducted. Results: In the study group 71% of pregnant women suffered from aggravation of varying severity deve¬loping on the background of symptoms of respiratory tract infection. Here with commitment to BT before and during pregnancy significantly did not differ. Inconsistency of BT to severity of the disease in 25% of women with mild and in 36% with moderate asthma course was detected.